New standard of proof for suicide at inquests in England and Wales. (29th July 2019) - Appleby, Louis; Turnbull, Pauline; Kapur, Nav; Gunnell, David; Hawton, Keith
Abstract : Suicide can now be concluded on "balance of probabilities"